Lead iodide perovskite light-emitting field-effect transistor - Chin, Xin Yu (2018)
Despite the widespread use of solution-processable hybrid organic–inorganic perovskites in photovoltaic and light-emitting applications, determination of their intrinsic charge transport parameters has been elusive due to the variability of film preparation and history-dependent device performance. Here we show that screening effects associated to ionic transport can be effectively eliminated by lowering the operating temperature of methylammonium lead iodide perovskite (CH3NH3PbI3) field-effect transistors. Field-effect carrier mobility is found to increase by almost two orders of magnitude below 200 K, consistent with phonon scattering-limited transport. Under balanced ambipolar carrier injection, gate-dependent electroluminescence is also observed from the transistor channel, with spectra revealing the tetragonal to orthorhombic phase transition. This demonstration of CH3NH3PbI3 light-emitting field-effect transistors provides intrinsic transport parameters to guide materials and solar cell optimization, and will drive the development of new electro-optic device concepts, such as gated light-emitting diodes and lasers operating at room temperature.